Territory and sustainable tourism development: A space-time analysis on European regions - Jo\~ao Rom\~ao; Jo\~ao Pedro Silva Martins Guerreiro; Paulo M. M. Rodrigues (REGION, 2017)
In the long run, tourism competitiveness depends on the sustainable use of territorial assets: the differentiation of destinations depends on the integration of cultural and natural resources into the tourism supply, but also on their preservation over time. The link between competitiveness and sustainability is the staring point for our analysis of the relationships between regional tourism competitiveness, the dynamics of tourism demand and investment and the existence of natural resources and cultural assets in European regions, by using advanced spatial econometric techniques. Despite the close relationship between tourism activities and the characteristics of the territory, the application of methods of spatial analysis methods in tourism studies is still scarce and the results of this work clearly show their potential for this field of research. Among the main findings of this paper, it was observed that natural resources do not have the expected positive impacts on regional tourism competitiveness and that European regions with more abundant natural resources are often developing unsustainable forms of mass tourism, with low value added and scarce benefits for the host communities. The existence of spatial correlation effects suggests that positive spillovers arising from tourism dynamics in neighbourhood regions prevail over potential negative effects related to the competition between destinations. Policy and managerial implications of these results are discussed and further research questions are suggested.
Keywords: 330; Cultural heritage; Natural resources; Endogenous resources; Spatial autocorrelation; Spatial econometrics; Competitiveness; Sustainability